Jazz - Tanner, Paul O.W. 1917-2013; Megill, David W.; Gerow, Maurice (Boston McGraw Hill, 1997)
"This outstanding introduction -- with an emphasis on listening -- provides you with an accessible and intriguing starting point for exploring the music, styles, and traditions of jazz."--Back cover
Listening to jazz -- Jazz heritages -- The blues -- Ragtime, 1900-1917 -- Dixieland, 1900-1920s -- Boogie-woogie, in the 1920s and 1930s -- Swing, 1932-1942 -- Bop, 1940-1950 -- Cool, 1949-1955 -- Hard bop, funky/straight-ahead jazz, circa 1954- -- Free form, avant-garde -- Crossover, third stream, Latin jazz -- Crossover, jazz fusion -- Appendix A. Listening suggestions -- Appendix B. Notational examples.
Includes bibliographical references (pages 219-222) and index.
Keywords: Jazz -- History and criticism